Interpretation of α-synuclein UV absorption spectra in the peptide bond and the aromatic regions - Saraiva, Marco A. (Journal of photochemistry and photobiology. B, Biology, 2020)
The interpretation of the UV absorption spectra of proteins was a matter of intense debate in the second half of the last century. The study of the spectroscopic characteristics of peptide bonds in proteins was then of particular interest but the absorption of a large number of peptide bonds in a protein is a complex subject which gathers many contributions such as those from other amino acid residues that absorb as well and therefore unequivocal proofs remains a challenge. This probably becomes the reason for being an almost untouched subject of study in the last 40 years or so. In this report the spectroscopic characteristics of the amyloid disordered protein α-synuclein (Syn) were studied in detail, concerning the UV absorption spectra in the peptide bond (200–230 nm) and the aromatic regions. Several protein concentrations, several solution pH and the first 300 min of the aggregation reaction were here investigated. In what the peptide bond region of Syn is concerned, UV difference spectra for a 33.5 μM protein solution concentration, in particular, revealed that at Syn solutions pH 7, 3 and 2 the counter-ion concentration increases in that order, as expected, accounting for the decrease of the peptide bond absorbance. Also, for this protein solution concentration, quantitative information can be obtained from peptide bond absorption and counter-ion concentration interplay in what the progression of the Syn aggregation reaction is concerned. This situation represents a label-free analysis of Syn aggregation in the lag-phase, in particular. Concerning the aromatic region of Syn, the UV absorption spectra revealed a perturbation at ca. 290–310 nm which is not related with light scattering effects in the UV absorption spectra but is related with the formation of mostly intermolecular hydrogen-bonded complexes between Syn tyrosyl groups and aspartic and glutamic acids residues. Interestingly, is the possible enrollment of these intermolecular complexes in the stabilization of this highly dynamic disordered protein in solution. •Early large α-synuclein aggregates populate the solutions.•Interpretation of α-synuclein UV absorption spectra.•Label-free analysis of α-synuclein aggregation.•Stabilization of α-synuclein by intermolecular contacts involving tyrosine residues.